Training In Making Supplementary Foods and Stunting Prevention Education Through Android-Based â€œAnak Sehatâ€ Digital Application at Kelurahan Petapahan, Lubuk Pakam Sub-District, Deli Serdang Regency - Eka Nugraha, Sony; Marianne; Keliat, Jane Melita (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Teaching, carrying out research for the development of science and applying knowledge, all three of which form a single unit known as the Tridharma of Higher Education. Community service is the third dharma of the Tridharma of Higher Education. The existence of community service is actually very important both for the management of the tertiary institution as well as for the existence of the tertiary institution in the community. The community service carried out is "Training on Making Complementary Food for Breastfeeding and Stunting Prevention Counseling Through the Android-Based "Healthy Children" Digital Application in Petapahan Village, Lubuk Pakam District, Deli Serdang Regency" The target group is mothers who have babies aged 12 months to 5 years in Posyandu Working area Petapahan Village, Lubuk Pakam District. Toddlerhood is an important period in the process of human development. Development and growth at that time determines the success of the growth and development of children in the next period. The period of growth and development at this age is a period that takes place quickly and will never be repeated, because it is often called the golden age or the golden age. Therefore, with this PkM activity, it can increase mother's awareness to pay attention to child development and prevent stunting.